2022
DOI: 10.3390/nano12203685
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Synthesis and Characterization of New Acrylamide Derivatives for Use as Corrosion Inhibitors in Nitric Acid Solutions of Copper

Abstract: The objective of this research was to explore the impact of corrosion inhibition of some synthetic acrylamide derivatives 2-cyano-N-(4-hydroxyphenyl)-3-(4-methoxyphenyl)acrylamide (ACR-2) and 2-cyano-N-(4-hydroxyphenyl)-3-phenylacrylamide (ACR-3) on copper in 1.0 M nitric acid solution using chemical and electrochemical methods, including mass loss as a chemical method and electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PP) as electrochemical methods. By Fourier-transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…On the basis of the charges of chelating atoms, inhibitors have been investigated to determine whether they stick to metallic surfaces. The likelihood that a metal’s d orbital will get an electron donation rises as the negative Mulliken charge of an adsorption site decreases . Mulliken charges for the lupine extract are broken down into carbon and heavy atoms (N and O).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the charges of chelating atoms, inhibitors have been investigated to determine whether they stick to metallic surfaces. The likelihood that a metal’s d orbital will get an electron donation rises as the negative Mulliken charge of an adsorption site decreases . Mulliken charges for the lupine extract are broken down into carbon and heavy atoms (N and O).…”
Section: Resultsmentioning
confidence: 99%
“…Ascorbic acid (vitamin C) concentration in fruits decreases with prolonged storage, as organic acids are consumed as substrates in respiration [75,89]. Despite this, the nanocoating material plus wax (wax + 100 ppm nanosilver) was better, as it kept the level of ascorbic acid above the control level throughout storage in both seasons (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the method of adsorption of the extract from a 1 M H 2 SO 4 on C-steel surface is an exothermic process by the negative ΔH ads sign that shows that the extract inhibition viability increments as the temperature increments. This behavior could be clarified by the reality that when temperature rises, more inhibitor particles adhere onto the metal surface [42], increasing the observed level of protection. The negative sign of the adsorption entropy (ΔS ads ) indicate that the disorder is reduced with the adsorption process [43,44].…”
Section: Adsorption Isothermmentioning
confidence: 99%